Pengembangan Infrastruktur Wisata Goa Tetes Sidomulyo: Langkah Menuju Pariwisata Berkelanjutan - Jannah, Aiga Nimang Valmai; Utami, Faricha Ajeng Mega; Firyal, Hana; Septian, Mohammad Irham; Ainul Haqqi, Muhammad Yusuf; Hasanah, Nur Lailatul; Fillaili, Zahrona; Yusrianti, Yusrianti (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Instant preparation of dragon fruit peel is an instant powder drink that comes from dragon fruit peel. Dragon fruit peel contains antiocyanin, vitamin C, vitamin E, vitamin A, alkaloids, terpenoids, flavonoids, thiamine, niacin, pyridoxine, cobalamin, phenolics, carotene and phytoalbumin which has function as antioxidants. The process of making instant dragon fruit peel powder drink preparations starts from the juice from the juice of dragon fruit peel which is cooked with sugar and low heat while stirring continuously to avoid caramelization. After drying and turning into powder, it is sieved and dried in an oven and then packaged to become the final instant product. Serve by dissolving 2 tablespoons of instant powder, then brewing it with 200ml hot water, then drinking it 2x a day for health maintenance and as an antioxidant. The community in Tawangsari Village is empowered to make and use dragon fruit peels into instant powder preparations so that they can utilize this waste into health products with economic value. They are also able to use the final product for their own consumption as a form of personal health maintenance.